2015
DOI: 10.1074/jbc.m114.612895
|View full text |Cite
|
Sign up to set email alerts
|

Ae4 (Slc4a9) Anion Exchanger Drives Cl− Uptake-dependent Fluid Secretion by Mouse Submandibular Gland Acinar Cells

Abstract: Background: Salivary glands exhibit a HCO 3 Ϫ -dependent fluid secretion mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 58 publications
9
59
0
Order By: Relevance
“…SLC4A9 is restricted to the basolateral membrane of acinar cells, where it participates in saliva secretion (86, 87) ( Figure 4B). SLC4A9 knockout mice displayed a 35% reduction in saliva secreted from the submandibular gland (86). This suggests that loss of SLC4A9 in cetaceans could contribute to a reduction of saliva secretion, which is in agreement with morphological observations that salivary glands are absent or atrophied in cetaceans (88,89).…”
Section: Loss Of An Ion Transporter Gene and Feeding In An Aquatic Ensupporting
confidence: 84%
See 2 more Smart Citations
“…SLC4A9 is restricted to the basolateral membrane of acinar cells, where it participates in saliva secretion (86, 87) ( Figure 4B). SLC4A9 knockout mice displayed a 35% reduction in saliva secreted from the submandibular gland (86). This suggests that loss of SLC4A9 in cetaceans could contribute to a reduction of saliva secretion, which is in agreement with morphological observations that salivary glands are absent or atrophied in cetaceans (88,89).…”
Section: Loss Of An Ion Transporter Gene and Feeding In An Aquatic Ensupporting
confidence: 84%
“…SLC4A9 encodes an ion transporter. 1) In the submandibular salivary gland, SLC4A9 participates in creating a transepithelial chloride anion flux into the acinar lumen, together with another transporter SLC12A2 and chloride channels (86). 2) This first evokes a passive movement of cations across the tight junctions into the acinar lumen.…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Peña‐Münzenmayer et al . 2015) have shown that AE4 is Na + dependent. SLC4A11. One of the BTR1 variants has a GXXXP motif.…”
Section: Discussionmentioning
confidence: 99%
“…Initial cloning of the gene demonstrated Cl – transport function of the protein, although phylogenetically this isoform is much more closely related to the Na + -coupled HCO 3 – transporters (Alka and Casey, 2014; Ko et al, 2002). Recent evidence suggests that AE4 functions as a Na + -dependent Cl – /HCO 3 – transporter in salivary glands, making AE4 distinct in its transport profile (Pena-Munzenmayer et al, 2015). AE3 is the primary Cl – /HCO 3 – exchanger in the brain, although AE2 is abundant in the choroid plexus (Hentschke et al, 2006; Romero et al, 2013).…”
Section: Acid–base Regulatory Mechanismsmentioning
confidence: 99%